2014
DOI: 10.1097/sle.0b013e31829015d2
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Cholecystostomy Versus Laparoscopic Cholecystectomy in Patients With Acute Cholecystitis and Failed Conservative Management

Abstract: In this matched cohort analysis, PC failed to show a significant reduction in morbidity compared with LC and was associated with a significantly longer hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 23 publications
1
9
0
1
Order By: Relevance
“…According to a Cochrane systematic review of randomized clinical trials, there was no significant difference seen in morbidity and mortality rates between the two interventions [7]. This was also seen in a retrospective single-institution study between drainage and surgical resection in high-risk patients regarding morbidity (17 vs. 9%, p = 0.67) and mortality (13 vs. 0%, p = 0.23), respectively [8]. It seems that the more recent data is more skewed towards surgical management [2], but given the lack of consensus among physicians and definitive evidence supporting certain criteria for selecting CTP over cholecystectomy in high-risk patients, this management decision is highly dependent on the individual physician’s clinical judgment.…”
Section: Discussionmentioning
confidence: 92%
“…According to a Cochrane systematic review of randomized clinical trials, there was no significant difference seen in morbidity and mortality rates between the two interventions [7]. This was also seen in a retrospective single-institution study between drainage and surgical resection in high-risk patients regarding morbidity (17 vs. 9%, p = 0.67) and mortality (13 vs. 0%, p = 0.23), respectively [8]. It seems that the more recent data is more skewed towards surgical management [2], but given the lack of consensus among physicians and definitive evidence supporting certain criteria for selecting CTP over cholecystectomy in high-risk patients, this management decision is highly dependent on the individual physician’s clinical judgment.…”
Section: Discussionmentioning
confidence: 92%
“…A total of 89 full‐text articles were assessed for eligibility, and 26 articles were included in the study. Details of relevant excluded studies are shown in Table S1 (supporting information). Of the 26 included articles, 24 were eventually used in the meta‐analysis, because four described the same two studies.…”
Section: Resultsmentioning
confidence: 99%
“…14 In these patients, early introduction of PCT may allow for easier and significantly shorter subsequent surgery. 14,45 Timing of PCT placement, removal and subsequent cholecystectomy…”
Section: Long Term Role Of Pctmentioning
confidence: 99%
“…12 This prevents the formation of adhesions, severe fibrosis and the destruction of anatomical tissue planes, which can make subsequent gallbladder surgery a challenging and at times dangerous endeavour. 14,45 From the available literature, it does seem that the answer to this question is 'as soon as possible'.…”
Section: Long Term Role Of Pctmentioning
confidence: 99%